Weighted Gene Co-expression Network Analysis Reveals Different Immunity but Shared Renal Pathology Between IgA Nephropathy and Lupus Nephritis - Jia, Ni-Ya; Liu, Xing-Zi; Zhang, Zhao; Zhang, Hong (Frontiers in Genetics, 2021)
Both IgA nephropathy (IgAN) and lupus nephritis (LN) are immunity-related diseases with a complex, polygenic, and pleiotropic genetic architecture. However, the mechanism by which the genetic variants impart immunity or renal dysfunction remains to be clarified. In this study, using gene expression datasets as a quantitative readout of peripheral blood mononuclear cell (PBMC)- and kidney-based molecular phenotypes, we analyzed the similarities and differences in the patterns of gene expression perturbations associated with the systemic and kidney immunity in IgAN and LN. Original gene expression datasets for PBMC, glomerulus and tubule from IgAN and systemic lupus erythematosus (SLE) patients as well as corresponding controls were obtained from the Gene Expression Omnibus (GEO) database. The similarities and differences in the expression patterns were detected according to gene differential expression. Weighted gene co-expression network analysis (WGCNA) was used to cluster and screen the co-expressed gene modules. The disease correlations were then identified by cell-specific and functional enrichment analyses. By combining these results with the genotype data, we identified the differentially expressed genes causatively associated with the disease. There was a significant positive correlation with the kidney expression profile, but no significant correlation with PBMC. Three co-expression gene modules were screened by WGCNA and enrichment analysis. Among them, blue module was enriched for glomerulus and podocyte (P < 0.05), and positively correlated with both diseases (P < 0.05), mainly via immune regulatory pathways. pink module and purple module were enriched for tubular epithelium, and correlated with both diseases (P < 0.05) through predominant cell death and extracellular vesicle pathways, respectively. In genome-wide association study (GWAS) enrichment analysis, blue module was identified as the gene module that distinguishes LN from systemic lupus erythematosus (SLE) and contains PSMB9, a susceptibility gene for IgAN. In conclusion, IgAN and LN showed different systematic immunity but similarly abnormal immunity in the kidney. Immunological pathways may be involved in the glomerulopathy and cell death together with the extracellular vesicle pathway, which may be involved in the tubular injury in both diseases. blue module may mask the causal susceptibility gene for IgAN and LN.